The Presentation of Students’ Critical Thinking Skill in Writing Essays with Microlearning Strategy and E-portfolios Integration - Ratih Laily Nurjanah (Yayasan Visi Intan Permata, 2025)
The microlearning strategy aims to overcome the decrease in students' span of focus, presenting learning materials in small portions due to technology exposure. E-portfolio aims to support students’ needs of involving technology in learning progress while developing critical thinking skills. This study aims to present the learning activities in writing essays based on the principles of microlearning while utilizing e-portfolios and describes the students’ critical thinking skills involved. The research was conducted as a case study involving a research diary observing the learning activities and critical thinking, and interview questions to gather students’ perceptions on their experiences utilizing microlearning and e-portfolio. The data were collected by performing observation in an Academic Writing class involving 80 students, and note-taking while learning happened in the classroom. Ten students were selected as respondents for further interview, and the responses were analysed with the thematic analysis technique. The findings showed that students took numerous small steps, starting from exploring a topic, elaborating a paragraph, and revising an essay before finally producing an essay. The students showed positive perceptions of the use of microlearning strategy and e-portfolios, saying that both were enjoyable and flexible. Various critical thinking skills shown by students during the process of essay writing were open-mindedness, communication, problem-solving, creativity, and analysis. It is important to view students’ small process and ensure students’ deep understanding of a topic instead of focusing on the final results.